2014
DOI: 10.11640/tjar.4.2014.03
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of XBRL Adoption on theInformation Environment: Evidence from Japan

Abstract: This article investigates whether and how the Japanese Financial Services Agency's mandatory use of XBRL affects investors in assessing financial information. Although regulators expect the introduction of XBRL to enhance the transparency and quality of business reporting, given the non-trivial implementation and learning costs, whether the XBRL-based disclosure reduces the information asymmetry between sophisticated and less-sophisticated investors remains an empirical question. As prior studies in other coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…Hodge et al (2004) and Pinsker & Wheeler (2009) found that investors who use existing technology well, such as XBRL, are better to interpret the information contained in financial statements than investors who do not use the technology. The previous studies found that XBRL adoption increases the transparency of firm financial statements (Bai et al, 2014;Kim et al, 2019;Kim et al, 2012;Pinsker & Li, 2008;Wang & Seng, 2014;Yen & Wang, 2015;Yoon et al, 2011).…”
Section: 4hypothesis Developmentmentioning
confidence: 97%
“…Hodge et al (2004) and Pinsker & Wheeler (2009) found that investors who use existing technology well, such as XBRL, are better to interpret the information contained in financial statements than investors who do not use the technology. The previous studies found that XBRL adoption increases the transparency of firm financial statements (Bai et al, 2014;Kim et al, 2019;Kim et al, 2012;Pinsker & Li, 2008;Wang & Seng, 2014;Yen & Wang, 2015;Yoon et al, 2011).…”
Section: 4hypothesis Developmentmentioning
confidence: 97%
“…Many empirical studies examined the role of the adoption of XBRL for shareholders (Premuroso & Bhattacharya, 2008;Tan & Shon, 2009;Yoon, Zo, & Ciganek, 2011;Kim, Lim, & No, 2012;Peng, Shon, & Tan, 2011;Bai, Sakaue, & Takeda, 2014;Hao, Zhang, & Fang, 2014;Kim, Li, & Liu, 2014;Tan & Shon, 2009;Shan & Troshani, 2014;Felo, Kim, & Lim, 2018;Blankespoor, 2019). For example, Yoon et al (2011) found that XBRL adoption improves the searching capability of investors and reduces information asymmetry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although some studies demonstrated that the adoption of the XBRL is very beneficial and has positive consequences (Hodge, Kennedy, & Maines, 2004;Tan & Shon, 2009;Yoon, Zo, & Ciganek, 2011;Chen, 2012;Bai, Sakaue, & Takeda, 2014;Markelevich, Shaw, & Weihs, 2015;Tzu-Yi et al, 2016;Blankespoor, 2019;Kumar, Kumar, & Dilip, 2019;Rahwani et al, 2019), there is still a need to examine the its usefulness at the country level (Nobre & Carvalho, 2011;Steenkamp & Nel, 2012). For example, Cong, Hao, and Zou (2014) provided empirical evidence that XBRL adoption improves stock market efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the XBRL International, on 2018 [1] about 8 million filers submit their filing using Extensible Business Reporting Language (XBRL) format to business registrars in 20 countries such as United State, Korea, China and Singapore. The unique tagging structure in XBRL has become the main reason this countries encouraged filing submission in XBRL format to make sure that the submitted reporting transaction are accurate, reliable, efficient in process and to promote new paperless environment [2][3] [4] [5].…”
Section: Introductionmentioning
confidence: 99%